Urgensi Program Calistung Metode Kreatif dalam Meningkatkan Kemampuan Membaca, Menulis dan Berhitung di SDN Mekarasih : Pengabdian - Yulia Nur Annisa; Ananda Bagus Satria; Asep Saepuloh; Destya Forcsa; Fadila Siti Nuraeni; Hapid Burhanudin; Melsandi; Nailah Sayyidatii Hayaa; Restiani; Vina Andriani; Yundani Irmala (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Reading, writing, and arithmetic (Calistung) are fundamental skills that are essential for elementary school students. However, many students still face difficulties in mastering these basic competencies. This study aims to describe the implementation of creative methods in Calistung learning at SDN Mekarasih and their impact on students’ literacy and numeracy skills. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings indicate that creative methods—such as word construction, number writing, number sequencing, and number comparison—successfully enhance students’ learning motivation and active participation. The study concludes that creative methods are proven effective as an instructional strategy for Calistung to foster literacy and numeracy interest among elementary school students.